Romidepsin in relapsed/refractory T-cell lymphomas: Italian experience and results of a named patient program. Issue 10 (2nd October 2016) - Zinzani, Pier Luigi; Pellegrini, Cinzia; Cerciello, Giuseppe; Monaco, Federico; Volpetti, Stefano; Peli, Annalisa; Angelucci, Emanuele; Corradini, Paolo; Cox, Maria Christina; Guarini, Attilio; Musso, Maurizio; Bresciani, Paola; et al.
Abstract: Clinical trial results indicate that romidepsin, a histone deacetylase inhibitor, is a promising treatment in relapsed/refractory T-cell lymphomas (TCLs). This retrospective multicenter study was conducted in patients with relapsed/refractory TCL treated with romidepsin monotherapy through a Named Patient Program (NPP) in Italy. Principal endpoints were overall response rate (ORR), safety, and overall survival (OS). The ORR in 33 evaluable patients was 24.2% with an ORR in the cutaneous TCL of 35.7%. Global OS was 39.3% at 30 months. There were not any specific differences on hematological and extrahematological adverse events. Data from patients treated with romidepsin outside a controlled clinical trial give additional information about the clinical use, efficacy, and toxicity of the drug given to relapsed or refractory TCL patients in a real life context as TCLs are rare diseases and more information is needed. These findings suggest that romidepsin is effective and safe for heavily pretreated TCL patients.